Measurement of D0-D [bar] 0 mixing parameters using D0→K0Sπ+π− and D0→K0SK+K- decays - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review letters, 2010)
We report a direct measurement of D0−¯¯¯D0 mixing parameters through a time-dependent amplitude analysis of the Dalitz plots of D0→K0Sπ+π− and, for the first time, D0→K0SK+K− decays. The low-momentum pion π+s in the decay D*+→D0π+s identifies the flavor of the neutral D meson at its production. Using 468.5 fb−1 of e+e− colliding-beam data recorded near √s=10.6 GeV by the BABAR detector at the PEP-II asymmetric-energy collider at SLAC, we measure the mixing parameters x=[1.6±2.3(stat)±1.2(syst)±0.8(model)]×10−3, and y=[5.7±2.0(stat)±1.3(syst)±0.7(model)]×10−3. These results provide the best measurement to date of x and y. The knowledge of the value of x, in particular, is crucial for understanding the origin of mixing.
Gesehen am 03.07.2023
Im Titel ist die Zahl "0" hochgestellt, der Buchstabe "S" ist tiefgestellt, im Titel steht der zweite Buchstabe "D" mit einem Oberstrich